Experimental and Numerical Analysis of Sandwich Panels Made of Different Core Materials with Plywood Facing - Ergün Güntekin; Mesut Uysal (Drvna Industrija)
Sandwich panels composed of different core materials with plywood facings were analyzed using experimental and numerical methods. Particleboard (PB), fiberboard (MDF), and foam materials were used as the core of the sandwich, while beech plywood was laid as the only face material. The layers of the sandwich were adhered with polyurethane adhesive. Elasticities (E) of PB, MDF, and plywood were determined in the laboratory. The E value specified by the manufacturer for the foam was used to determine the flexural behavior of sandwich panels. Results of the study indicated that the type of core material significantly affects the bending behavior of sandwich panels with plywood facings. Sandwich panels with MDF-core were observed to be more resistant in bending compared to PB and foam-core sandwich panels. Core shear failure was the dominant failure type when wood-based materials were used as core material. Buckling or tension in facing was observed when foam was used as core material. The results of the study demonstrate that numerical models can be used to accurately predict the bending behavior of the sandwich panels until failure based on yield stress and tangent modulus of the materials.